Fluorescence switching with subphthalocyanine-dihydroazulene dyads. Issue 1 (21st January 2019) - Gotfredsen, Henrik; Kilde, Martin Drøhse; Santella, Marco; Kadziola, Anders; Nielsen, Mogens Brøndsted
Abstract : The boron subphthalocyanine (SubPc) fluorescence is reversibly modulated by photoisomerization of a covalently attached dihydroazulene (DHA) photoswitch into a vinylheptafulvene (VHF). Abstract : One convenient way of reversibly modulating the emission properties of a fluorophore is by introducing a photochromic unit that upon irradiation is converted into an isomeric unit that can quench the fluorescence of the fluorophore. Here we present the synthesis of two dyads containing a boron subphthalocyanine (SubPc) fluorophore and the dihydroazulene (DHA) photoswitch. Upon photoisomerization, the DHA unit is converted to a vinylheptafulvene (VHF) unit that was found to efficiently quench the SubPc fluorescence when placed at the axial boron position of the SubPc. The original fluorescence was restored by thermal conversion of the VHF to DHA. Fluorescence was thereby turned off and on by successive light-heat cycles. The other dyad has the DHA unit placed at the periphery of the SubPc, and this dyad showed instead limited photostability.